“Aquí pasan cosas raras”: miedo, vergüenza y culpa en algunos relatos de Luisa Valenzuela - Cerda, Susana (Verbum – Analecta Neolatina, 2014)
In the collection of short stories Aquí pasan cosas raras, Luisa Valenzuela portrays a world that reflects the reality of state terrorism in Argentina during the 70’s and 80’s. The aim of this paper is to examine and explore how the representation of emotions such as fear, guilt, and shame invites us to think about the relationship between the victim and the victimizer. I argue that some of Valenzuela’s literary representations are helpful to understand what Hanna Arendt suggests on the banality of evil, and what Martha Nussbaum’s emphasises about the fragility of goodness.